Metaverse sebagai Paradigma Baru: Implikasi Terhadap Bisnis dan Sistem Informasi (Journal Digital Technology Trend, 2023)
This research explores the implications of the metaverse as a new paradigm for business and information systems, utilizing qualitative and quantitative approaches to gain a comprehensive understanding. Surveys and in-depth interviews were conducted with business actors, information system professionals, and metaverse users. The findings indicate that 75% of respondents are familiar with the metaverse, and 40% have implemented this technology in their businesses. Metaverse implementation has been shown to increase customer engagement and sales by 70% and 60%, respectively. However, challenges such as security, privacy issues, and high implementation costs remain significant barriers. The study also highlights the need for advanced technological infrastructure and interoperability standards to support the integration of the metaverse in business. In conclusion, the metaverse holds great potential to transform the way we interact, work, and conduct business, with the right strategies and effective collaboration.